"Body stuffing" and "Body packing" – Forensic control of human excrements in police custody in Hamburg, Germany. (November 2021) - Mushumba, Herbert; Schröder, Ann Sophie; Sperhake, Jan-Peter; Ondruschka, Benjamin; Püschel, Klaus
Highlights: Controlled defecation is a safe method used to confiscate evidence when body packing and body stuffing are suspected. Negative drug toilets should not always imply that a suspected drug dealer did not ingest any drugs. Body packers and body stuffers are predominantly male and relatively young individuals. Abstract: Introduction: Different methods are used to confiscate evidence whenever suspected body packers or body stuffers are taken into custody. Among these, controlled defecation and analysis of drug toilets from suspects has proved to be safe given that no invasive or forceful procedures are applied. Materials and methods: All records of "drug toilet" evaluations done at the Hamburg Institute of Legal Medicine from January 1st 2018 to April 30th 2021 were descriptively analyzed for the individual's age, sex, country of origin, and whether the drug toilets contained any drug "balls", packages or containers. In case of a positive finding, the total number of balls found were recorded. Special cases are presented in detail for illustrative purposes. Results: Drug toilets from 72 suspects were examined in the period under review. 98.6% (n = 71) of the suspects were males and relatively young with approximately two-thirds (62.5%, n = 45) aged 34 years or below (range 18–50 years). The majority of suspects originated from African countries (72.2%, n = 52). The typical drug balls or containers were found in 13 (18.1%) of the examined drug toilets. Conclusion: Negative drug toilets might indeed indicate that the suspect had not ingested any drug packages at the time of arrest or while in custody. However, multiple excretions, voluntary delay of defecation, use of drugs to delay the excretion process or even individual differences in excretion times are possible, and therefore, a negative drug toilet should not always imply with certainty that the individual in question had not ingested any drugs.